Assessment of midwives’ practices during the active phase of labour in the primigravid in the first stage of childbirth - خضر رنا; عيسى دونا; عفاف نظام (Latakia University Journal -Medical Sciences Series, 2023)
Women during labor and delivery need good and skilled nursing care by midwives to improve pregnancy outcomes and protect the woman and her baby from complications. Therefore, our current descriptive study aimed to identify the level of midwives’ practices during the first phase of labor for 75 midwives who were selected using the convenient sample method from the labor departments of Martyr Majd Abdullah Hospital in Tartous Governorate, and data were collected using a tool designed by the researcher. The results showed that the midwives’ practices were good during the active phase of labour. Most of midwives applied " Dressing the lady in the hospital dress", "monitoring uterine contractions in terms of strength and frequency", "cervical assessment", and "lying down dorsal position with a slight bend of the knees" to check the fetal pulse and check the dilation and erasure of the cervix. While most of them partially applied "preparing the tools, explaining the procedure to the labor", while most did not apply "the use of cold and warm compresses" in the perineum, and massage to the head, limbs, neck and shoulders. The study recommended educating midwives on standards for caring for women during active labour, designing a guide to international standards, and conducting research on their practices during other stages of labour.